2017
DOI: 10.1038/nphys4278
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Klein-like tunnelling of high-temperature superconducting pairs into graphene

Abstract: Superconductivity can be induced in a normal material via the 'leakage' of superconducting pairs of charge carriers from an adjacent superconductor. This so-called proximity e ect is markedly influenced by graphene's unique electronic structure, both in fundamental and technologically relevant ways. These include an unconventional form 1,2 of the 'leakage' mechanismthe Andreev reflection 3 -and the potential of supercurrent modulation through electrical gating 4 . Despite the interest of high-temperature super… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 28 publications
4
50
0
Order By: Relevance
“…Experiments have mostly focused on conventional low critical temperature (T C ) superconductors with s-wave pairing. Despite early theoretical studies showing that d-wave (high-T C ) superconductors should lead to novel directional effects [12,13] and exotic pairing [14,15], evidence for unconventional superconductivity in graphene has been found only recently [16,17]. Scanning electron tunneling microscopy (STM) of graphene on Pr 2-x Ce x CuO 4 revealed a superconducting gap [16] and spectral features suggesting (p-wave) superconductivity induced in graphene.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments have mostly focused on conventional low critical temperature (T C ) superconductors with s-wave pairing. Despite early theoretical studies showing that d-wave (high-T C ) superconductors should lead to novel directional effects [12,13] and exotic pairing [14,15], evidence for unconventional superconductivity in graphene has been found only recently [16,17]. Scanning electron tunneling microscopy (STM) of graphene on Pr 2-x Ce x CuO 4 revealed a superconducting gap [16] and spectral features suggesting (p-wave) superconductivity induced in graphene.…”
mentioning
confidence: 99%
“…Scanning electron tunneling microscopy (STM) of graphene on Pr 2-x Ce x CuO 4 revealed a superconducting gap [16] and spectral features suggesting (p-wave) superconductivity induced in graphene. Experiments on YBa 2 Cu 3 O 7 (YBCO) and chemical-vapordeposited (CVD) graphene devices by some of us [17] showed transparent superconductor-graphene interfaces and clear evidence of Andreev reflection. Interestingly, we also found that the Andreev electron-hole pair transmission can be modulated by a back-gate voltage, through a mechanism analogous to the Klein tunneling [18].…”
mentioning
confidence: 99%
“…However, until recently, the fabrication of graphene/YBCO contacts and their superconducting proximity effect have been reported, where both the temperature dependence and the current bias dependence of resistance for the contacts are investigated [19], showing the indication of the tunneling of Cooper pairs from YBCO to the graphene. The ZBCP and so-called Klein-like tunneling of Andreev electron-hole pairs that carry superconducting correlations from the high-T c SC YBCO into graphene have also been experimentally observed very recently [20], as in the usual Klein tunneling with the reflectionless transmission of electrons across a high energy barrier. Moreover, the latest experimental findings show the realization of the intrinsic unconventional superconductivity in a 'magic angle' twisted bilayer which is created by stacking two sheets of graphene that are twisted relative to each other by a small angle [21].…”
Section: Introductionmentioning
confidence: 90%
“…Finally, we comment the execution of the present graphene-based FM/RSOC/I/d-wave SC junction. The proximity-induced d-wave superconductivity in graphene could be attained by YBCO films grown on SrTiO 3 [19,20]. As the YBCO films own very high T c , one can study the proximity effect of graphene above the liquid nitrogen temperature, which favors the easily experimental performance.…”
Section: Experimental Realizationmentioning
confidence: 99%
See 1 more Smart Citation